PEMEROLEHAN BAHASA PADA ANAK USIA TIGA TAHUN - Dian Syahfitri (Balai Bahasa Sumatera Utara, 2019)
The first three years of a child‟s life is the golden age for a child‟s growth and development. Therefore, this age range became interesting to research the stage of achievement of what works performed by three years old child in terms of language acquisition. The subject of observation, Azra 3 years old with focus on the subject of language development in terms of phonological, syntax, semantics. The reserach found the children three years old mastering the overall sound of the vocal but some sounds diphtongs. In the consonant sounds there are still barries to the sound /r/ and /s/. In terms of syntax, the achievement of children in forming a sentence like: declarative, imperative, interrogative, and complex sentences have resembled an adult sentence, although there are some mistakes that are generally still acceptable. Finally , in terms of semantics subject still have difficulty in understanding the description of time .